Chlorogenic acid ameliorates chronic stress-induced prefrontal cortex injury through activating the 5-HT/BDNF signaling pathway in rats. (December 2022) - Zhao, Shuping; Yang, Tianyuan; Hou, Xiaoyu; Zhang, Haiyang; Zhao, Yuan; Wang, Hui; Sun, Ning; Tan, Haoyang; Zhang, Jiuyan; Fan, Honggang
Abstract: The chlorogenic acid (CGA) has a strong neuroprotective ability and cognitive improvement. The purpose of this study was to investigate the effect and mechanism of CGA on chronic restraint stress (CRS)-induced prefrontal cortex (PFC) injury and depression-like behavior. Rats were restrained for 6 h each day to create a CRS paradigm that lasted for 21 days. One hour prior to constraint, CGA (50 mg/kg, 100 mg/kg and 150 mg/kg) was intragastrically delivered. The results showed that CGA could reduce serum corticosterone (CORT) levels in rats and 100 mg/kg CGA could prevent CRS-induced depression-like behaviors. Histopathological revealed that 100 mg/kg CGA ameliorated CRS-induced PFC microstructural. Furthermore, 5-HT content was also increased. Therefore, 100 mg/kg of CGA will be used to further probe the molecular mechanism of regulating 5-HT. Observations using transmission electron microscopy demonstrated that CGA reduced CRS-induced PFC synaptic damage. CGA promotes cAMP-CREB-BDNF signaling pathway and inhibits indoleamine 2, 3-dioxygenase (IDO) and serotonin transporter (SRET). Cellular thermal shift assays (CETSA) and molecular docking studies have shown that IDO, SERT and CGA docking have priority potential targets. Together, a protective effect of CGA is seen in rats with CRS-induced PFC by regulating the expression of IDO and SERT and then affecting the effect of 5-HT on the cAMP-CREB-BDNF signaling pathway. Graphical abstract: Image 1 Highlights: Chlorogenic acid protects rat prefrontal cortex from chronic stress-induced injury. Chlorogenic acid improves 5-HT content and relieve depression-like behavior in rats. 5-HT can act on cAMP-CREB-BDNF signaling pathway. IDO, SERT can be potential therapeutic targets of chlorogenic acid.